ING4 inhibits the translation of proto‐oncogene MYC by interacting with AUF1. Issue 11 (19th April 2013) - Lu, Meiling; Pan, Chunyang; Zhang, Lantian; Ding, Chenhong; Chen, Fei; Wang, Qinwan; Wang, Kesheng; Zhang, Xin
Abstract : The ING4 tumor suppressor plays a significant role in various cancer‐related cellular processes. AUF1 affects the stability and/or translation of multiple mRNAs via binding to an AU‐rich element in the 3′‐untranslated regions. In this study, we identify AUF1 as a novel and direct binding partner of ING4. mRNP immunoprecipitation assays indicated that ING4, AUF1 and MYC mRNA present in the same mRNP complex. ING4 suppressed MYC protein expression without altering MYC mRNA levels, and abolished the cell proliferation induced by AUF1 in K562 cells. These results suggest that ING4 may regulate MYC translation by its association with AUF1. Abstract : ING4 directly interacts with AUF1. ING4, AUF1 and MYC mRNA are in the same mRNP complex. ING4 decreases MYC protein levels without affecting MYC mRNA levels. ING4 abolishes the cell proliferation induced by AUF1. The NLS region of ING4 is essential for ING4 association with AUF1.